PENGARUH DISIPLIN KERJA, PENGALAMAN KERJA DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. BIRO KLASIFIKASI INDONESIA (BKI) CABANG RIAU - Daulay, Irfansyah (Eko dan Bisnis: Riau Economic and Business Review, 2016)
This research was conducted at PT. Indonesian Classification Bureau Pekanbaru Branch is located at Jl. Arifin Ahmad Pekanbaru. The purpose of this study to analyze the effect of work discipline, work experience and partial compensation on employee productivity PT. Riau branch of the Indonesian Classification Bureau and to analyze the influence of labor discipline, work experience and simultaneous compensation of employee productivity PT. Riau branch of the Indonesian Classification Bureau. To achieve these objectives do research using a sample of 57 people, using census method. Data analysis method using simultaneous test and partial test (multiple linear regression analysis with SPSS Windows version 17).Based on the results of hypothesis testing, it is found that the work discipline variables obtained t count> t-table on significant alpha = 5%, which amounted to 2,004 (2,638> 2,004). Based on the test results in variable work experience is seen that t count> t-table (2,209> 2,004). Based on the test results in variable compensation can be seen that t count> t-table (3,246> 2,004). Thus it can be concluded that the variable work discipline, work experience and partial compensation have a strong influence in affecting the productivity of employees at PT. Society Indonesia (BKI) Branch Riau.Based on the test results F-count amounted to 32 427 (see attachment) and F-table with a significant level of 5% = 2,779 (see annex). Then obtained the F-count is greater than F-table (32 427> 2.779). Thus the hypothesis that work discipline, work experience and compensation is a factor that affects the productivity of employees at PT. Society Indonesia (BKI) received Riau Branch.Recommendations to the authors propose is At the company, in order to further enhance the working discipline variable where of respondents on indicators of exemplary leadership and human relations received a low response from respondents with low respondents in these indicators will affect employees in improving their work productivity